Optimalisasi Produksi Keripik Jamur dengan Metode Nawaz Enscore Ham (NEH), Long Processing Time (LPT) Dan Shortest Processing Time (SPT) - Ridho Ananda; Saufik luthfianto; Al Atsary, Arry Darmawan (Jurnal Ilmiah Ilmu dan Teknologi Rekayasa, 2022)
. The agricultural sector is one of the supporting factors for Indonesia's economic development, one of the profitable agricultural activities is mushroom cultivation. The mushroom commodity agro industry is certainly inseparable from production activities in producing products such as mushroom chips. The problem to be solved in this research is to optimize the production process time at each work station with the criteria of minimizing makespan. In this study, the NEH, LPT and SPT methods will be used to solve the problem of scheduling the production of mushroom chips in IKM XYZ. These methods were chosen because they fit the conditions at IKM XYZ, namely: the flowshop production process. The results obtained at the processing stage of mushroom chips, the comparison between the 3 scenario methods used produces the best makespan value in scenario 2 in the NEH method with a value of 2204 minutes compared to the actual scheduling with a makespan value of 2652 minutes the difference in makespan value of the two methods is 15.8 %. For the calculation of waste in the production of mushroom chips, the largest waste is in the waiting process, which is 30 and the movement does not need to be 24. The profit analysis between the actual FCFS method and the proposed NEH Scenario 2 produces a different amount of profit, in the actual method the profit obtained in the production of 4000 pcs mushroom chips Rp.1680,000 while the proposed method is Rp. 3,320,000.